Bacteria-responsive multilayer coatings comprising polycationic nanospheres for bacteria biofilm prevention on urinary catheters. (15th March 2016) - Francesko, Antonio; Fernandes, Margarida M.; Ivanova, Kristina; Amorim, Sara; Reis, Rui L.; Pashkuleva, Iva; Mendoza, Ernest; Pfeifer, Annett; Heinze, Thomas; Tzanov, Tzanko
Graphical abstract: Abstract: This work reports on the development of infection-preventive coatings on silicone urinary catheters that contain in their structure and release on demand antibacterial polycationic nanospheres. Polycationic aminocellulose conjugate was first sonochemically processed into nanospheres to improve its antibacterial potential compared to the bulk conjugate in solution (ACSol ). Afterward the processed aminocellulose nanospheres (ACNSs ) were combined with the hyaluronic acid (HA) polyanion to build a layer-by-layer construct on silicone surfaces. Although the coating deposition was more effective when HA was coupled with ACSol than with ACNSs, the ACNSs -based coatings were thicker and displayed smoother surfaces due to the embedment of intact nanospheres. The antibacterial effect of ACNSs multilayers was 40% higher compared to ACSol coatings. This fact was further translated into more effective prevention of Pseudomonas aeruginosa biofilm formation. The coatings were stable in the absence of bacteria, whereas their disassembling occurred gradually during incubation with P. aeruginosa, and thus eradicate the biofilm upon release of antibacterial agents. Only 5 bilayers of HA/ACNSs were sufficient to prevent the biofilm formation, in contrast to the 10 bilayers of ACSol required to achieve the same effect. The antibiofilm efficiency of (HA/ACNSs )10 multilayer construct built on a Foley catheter was additionally validated under dynamic conditions using a model of the catheterized bladder in which the biofilm was grown during seven days. Statement of Significance: Antibacterial layer-by-layer coatings were fabricated on silicone that efficiently prevents Pseudomonas aeruginosa biofilm formation during time beyond the useful lifetime of the currently employed urinary catheters in medical practice. The coatings are composed of intact, highly antibacterial polycationic nanospheres processed from aminated cellulose and bacteria-degrading glycosaminoglycan hyaluronic acid. The importance of incorporating nanoscale structures within bacteria-responsive surface coatings to impart durable antibacterial and self-defensive properties to the medical indwelling devices is highlighted.